Conceptual Metaphors in Perfume Product Reviews on the TikTok Online Platform - Kusnadi, Gilang (Allure Journal, 2026)
This study examines the use of conceptual metaphors in perfume product reviews on the TikTok platform, focusing on gender-based representational differences. Using a qualitative descriptive approach, data were collected from six TikTok accounts three male and three female perfume reviewers based on video content published between May and June 2025. The data consist of verbal expressions used to describe fragrance characteristics, performance, and experiential impressions, which were transcribed and analyzed through conceptual metaphor theory and conceptual blending theory. The findings indicate that female reviewers predominantly employ emotional, narrative-driven metaphors that construct imaginative and atmospheric representations of perfumes, emphasizing mood, aesthetics, and sensory imagination. In contrast, male reviewers tend to use metaphors centered on functionality, projection, strength, and situational suitability, frequently drawing on source domains related to physical force, sound, and performance. These patterns demonstrate how metaphor functions as a cognitive mechanism that enables reviewers to conceptualize and communicate abstract olfactory experiences that cannot be directly accessed through digital media, rather than merely serving decorative linguistic purposes. Furthermore, the interaction of sensory, emotional, and cultural domains highlights the role of conceptual blending in generating novel meanings in digital fragrance discourse. The study also reveals that reviewers’ metaphorical choices, evaluative focus, and communicative tone reflect gender identity, indicating a close relationship between metaphor usage and identity performance in online environments. Overall, this study enriches cognitive linguistic research on digital discourse, provides insights into gendered language practices in social media marketing, and deepens our understanding of non-visual sensory product representations on online platforms.